Experimental study of the high-power laser resistance of ablative material-filled sandwich panels with truss cores under hypersonic airflow. (1st December 2022) - Yuan, Wu; Wang, Jiangtao; Wang, Ruixing; Wang, Zhe; Song, Hongwei; Huang, Chenguang
Highlights: The performance of ablative material filled sandwich panels with truss cores under the combined high-power local heat flux and hypersonic airflow is firstly investigated experimentally. The strength of the ablative material filled sandwich panels with truss cores is superior compared with other kinds of thermal protection structures. Effects of hypersonic airflow on the performance of ablative material filled sandwich panels are revealed. Abstract: In this study, the performance of ablative material-filled sandwich structures with truss cores under laser irradiation is experimentally analyzed in a hypersonic wind tunnel. As a comparison, we investigated the responses of a monolithic high-temperature alloy plate, unfilled sandwich panel, and thermal insulating material-filled sandwich panel. Failure times and ablation morphologies are assessed using a high-speed camera, while temperature histories are obtained using a colorimetric pyrometer. Experimental results show that, when subjected to a transverse hypersonic airflow, the laser resistance of the ablative material-filled sandwich structures is substantially better than that of other structures. Compared to a static environment, failure times of the sandwich structures in the hypersonic airflow are reduced due to the mechanical erosion effect. The detailed action mechanisms of the ablative material-filled sandwich structures are revealed by numerical modeling and the characterization of the ablation morphology.